2014
DOI: 10.1093/ejcts/ezu077
|View full text |Cite
|
Sign up to set email alerts
|

Early and mid-term outcomes of trans-sternal and video-assisted thoracoscopic surgery for thymoma

Abstract: VATS thymectomy for thymoma is feasible, safe and has comparable mid-term oncological outcomes to trans-sternal thymectomy. Future research is required to evaluate long-term oncological outcomes of VATS thymectomy for thymoma in national registries and randomized, controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
36
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 23 publications
9
36
0
7
Order By: Relevance
“…9 Both unilateral and bilateral videothoracoscopic surgical techniques are gaining in popularity based on the benefits of shorter LOS and relatively fewer surgical complications without compromising therapeutic outcomes when compared with trans-sternal thymectomies. 2 In an attempt to improve on these benefits, use of a robotic-assisted surgical system was implemented for the first time in the resection of a mediastinal surgery controls. 5 Augustin et al 5 demonstrated that robotic-assisted thymectomy had similar LOS (2-5 days) and overall shorter operative times than videothoracoscopic surgery thymectomies reported in the literature.…”
Section: Thymectomymentioning
confidence: 99%
“…9 Both unilateral and bilateral videothoracoscopic surgical techniques are gaining in popularity based on the benefits of shorter LOS and relatively fewer surgical complications without compromising therapeutic outcomes when compared with trans-sternal thymectomies. 2 In an attempt to improve on these benefits, use of a robotic-assisted surgical system was implemented for the first time in the resection of a mediastinal surgery controls. 5 Augustin et al 5 demonstrated that robotic-assisted thymectomy had similar LOS (2-5 days) and overall shorter operative times than videothoracoscopic surgery thymectomies reported in the literature.…”
Section: Thymectomymentioning
confidence: 99%
“…Ye et al (41) demonstrated that the oncological outcomes were comparable for TT and OT groups. Manoly et al (42) concluded that the DFS was comparable between the groups. Several reports demonstrated that there was no significant difference in the DFS between the groups (43,49).…”
Section: Surgical Treatmentmentioning
confidence: 96%
“…patients, and on the hypothetical risk that a second primary thymoma may develop in the residual thymus gland (4,7). However, an increasing number of reports over the recent years have shown that thymectomy can be accomplished safely and effectively by VATS both for early-stage thymoma and for MG (8)(9)(10)(11)(12)(13)(14).A recently published propensity-matched study on patients undergoing either trans-sternal or minimally invasive thymectomy for stage I-II thymoma showed overall postoperative complications rates to be lower with VATS thymectomy, and suggested that in fact, the majority of complications in the open group were due the complications of median sternotomy (15).There are no randomized trials that compare minimally invasive and open thymectomy, but VATS thymectomy was compared to the traditional open approach in two recent large meta-analyses (16,17). Both such studies showed significantly reduced postoperative blood loss and blood products requirements, reduced postoperative pain scores, reduced overall complications rates and reduced postoperative hospital stay with VATS thymectomy compared with open thymectomy.…”
mentioning
confidence: 99%
“…patients, and on the hypothetical risk that a second primary thymoma may develop in the residual thymus gland (4,7). However, an increasing number of reports over the recent years have shown that thymectomy can be accomplished safely and effectively by VATS both for early-stage thymoma and for MG (8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%